Critical anatomic region of nasopalatine canal based on tridimensional analysis: cone beam computed tomography - Fernández-Alonso, Ana (Sci Rep, 2015)
The study aim of this was to define the critical anatomic region of the premaxilla by evaluating dimensions of nasopalatine canal, buccal bone plate (BBP) and palatal bone plate (PBP). 230 CBCTs were selected with both, one or no upper central incisors present (+/+, −/+, −/−) and periodontal condition was evaluated. T-student test, ANOVA, Pearson´s correlation and a multivariant-linear regression model (MLRM) were used. Regarding gender, significant differences at level 1 (lower NC) were found for: buccal-palatal, transversal and sagittal NC diameters, and NC length (NCL). Regarding dental status, significant differences were found for: total BBP length (tBL) and PBP width (PW2) at level 2 (NCL midpoint). NCL was correlated with PW2, tBL, and PBP length at level 3 (foramina of Stenson level). An MLRM had a high prediction value for NCL (69.3%). Gender is related to NC dimensions. Dental status has an influence on BBP dimensions, but does not influence on NC and PBP. Periodontal condition should be evaluated for precise premaxillae analysis NC diameters at the three anatomical planes are related to each other, while NCL is related to BBP and PBP lengths. A third of premaxilla is taken up by NC, thus, establishing the critical anatomic region.